Assessment of clinico-radiological and biochemical markers of rickets: A hospital based prospective follow up study - Kumar, Sanjay; Jyoti, Abha; Chaurasiya, Tushar; Kumar, Rajesh; Khan, Nadeem Ashraf (Asian Journal of Medical Sciences, 2021)
Background: Rickets is a disorder of defective mineralization due to deficiency of calcium and vitamin D and is more prevalent amongst the developing nations. Rickets has been ranked amongst the five most prevalent diseases in children of developing countries. The diagnosis of rickets is based on clinical features, biochemical studies and radiological signs and confirmed by response to treatment.Aims and Objectives: The purpose of this study is to evaluate the clinical, radiological and biochemical markers of the rickets by measuring the markers at the time of presentation, at 6 weekly intervals and after completion of treatment with standard regimen for rickets.Materials and Methods: 101 cases of nutritional rickets in age group 6 month to 18 years were allocated to receive combination therapy of calcium and vitamin-D according to their age and weight during a study period of 24 weeks. Radiographs (wrist and knee) and biochemical parameters (serum calcium, inorganic phosphate, alkaline phosphatase [ALP], and Vitamin-D), as well as clinical features, were evaluated at presentation, 6, 12, 18, and 24 weeks and response of treatment and markers were assessed at subsequent interval. clinical, radiological, biochemical parameters were evaluated statistically with Chi-square test for qualitative and 2 or more different variables by ANOVAs respectively. A P